The dynamic behaviors of a bubble in a confined domain. (1st November 2017) - Liu, N.N.; Ming, F.R.; Liu, L.T.; Ren, S.F.
Abstract: The oscillation of a bubble near the free surface confined by a cylindrical tank is simulated by the axisymmetric boundary integral method (BIM) code. Firstly, the axis-symmetrical numerical modeling is established based on the incompressible potential flow theory, which is followed by the validation with mechanism experiments carried out using the spark-generated bubble equipment and its auxiliary system, e.g., the high-speed camera. Good agreements are achieved between the numerical results and the experimental ones. Afterwards, the dynamics of a bubble near the free surface in a cylindrical tank and its induced pressure on the tank wall are investigated. Due to the existence of tank solid wall, the water skirt is advanced to form at the bubble expansion stage rather than at the bubble toroidal stage for the case of no tank. In addition, the effects of tank radius on the bubble motion are discussed and a critical radius for negligible effects is obtained. Finally, the bursting at the free surface and the exposure at the bottom induced by the bubble are also studied to provide a reference for underwater explosions of the shallow or the tank experiments. Highlights: The improved 4π rule is introduced in the boundary integral method (BIM) to solve the confined domain problem. A critical distance for negligible effects on bubble oscillation and bubble bursting in a confined domain is found. The existence of adjacent tank boundary advances the formation of the water skirt rather than the case of no tank. An interesting phenomenon called 'bottom wall effect' is observed when γ w ∗ is below 0.8.